Lifestyle of chilean medical students during the covid-19 pandemic: Estilo de vida de estudiantes de medicina chilenos durante la pandemia por covid-19 - Cáceres Codoceo, Ana Belén (2021)
Objective: To analyze the relationship of lifestyle and habits associated with health care and religiosity in Chilean Adventist medical students during the COVID-19 pandemic. Methods: Analytical and cross-sectional, census, non-experimental design. The population consisted of 72 Adventist medical students who attended or are in any year of the career in 2020 and 2021. The FANTASTIC instrument was applied, in its validated version, and an evaluation of habits associated with health care and religiosity. The work was approved by an ethics committee. Results: 55.6% are female. The mean age is 22.64. 43.1% of the students have some type of diet associated with vegetarianism. Tobacco use was not evidenced. 66.7% study the Bible and pray always or almost always. 77.8% of the students have a very good or fantastic lifestyle. When performing the Spearman correlation between the variable habits associated with health care and religiosity versus the total score of the FANTASTICO instrument, a statistically significant relationship is presented at the 0.01 level (p <0.00 r=0.48). Conclusions: Although some habits can be improved, in general most of the students have a very good lifestyle. It is appreciated that the scores of habits associated with health care and religiosity have a positive relationship with the scores obtained in the fantastic instrument.